Treinamento de força de baixa intensidade realizado até a falha muscular ou próximo à falha não promove ganhos adicionais de força, hipertrofia muscular e funcionalidade de idosos - Bergamasco, João Guilherme Almeida (2019)
Background: The present study compared the effects of low-load resistance training (RT) protocols performed to failure (FAI), to voluntary interruption (VOL) or lower-volume fixed repetitions (FIX) on muscle strength, hypertrophy and functionality in older adults. Methods: Forty-one older adults (60-77 years) were randomized into three RT groups: FAI, VOL and FIX. The three groups completed 12 weeks of RT at 40% of the one-repetition maximum (1-RM). Training protocols involved three sets in knee extension, leg press and leg curl, performed twice a week, in which in FAI protocol repetitions were performed to muscle failure, in VOL, repetitions were performed to voluntary interruption and FIX performed 10 repetitions per set. Muscle strength was measured through 1-RM, cross-sectional area (CSA) by ultrasonography and functionality through chair stand (CS), habitual and maximal gait speed (HGS and MGS, respectively), timed up-and-go (TUG) and 6-minute walking test (6MWT). All the assessments were performed pre- and post-training. Results: The results showed similar increases from Pre to Post in 1-RM values for all groups (P < 0.0001). There were no significant increases in CSA. Additionally, all groups demonstrated significant and similar increases in CS and HGS and there were no significant changes in MGS, TUG and 6MWT for any group. Conclusions: Low-load protocols do not require to be performed to muscle failure or near failure to promote significant improvements in strength and some of the functional parameters in initial stages of training in older adults.